PERENCANAAN STRUKTUR JEMBATAN CABLE STAYED DENGAN TWO VERTICAL PLANES SYSTEM TIPE FAN (STUDI KASUS JEMBATAN KEMBAR MAHAKAM IV) - NUR, ANGGA ALFIAN (KURVA S JURNAL MAHASISWA, 2017)
Bridge is a construction aim to connect two piece of paths that caused of obstacles such as valley, river, sea, lake, irrigation channel, train track, etc. Mahakam IV Twin Bridge in Samarinda City is an Arch Bridge or cur ve steel who placed right beside Mahakam I bridge with the main span about 220 M and two side spans about 90 M each.Cable Stayed Bridge is composed of pylon element, girder, and conducted from cables that connect to pylon and girder it selves. This cable distributes it force from girder or bridge floor that caused of traffic load and dead load to pylon bridge.Curve Steel Bridge holds such strong load it selves, even more it lives load too as a national road with a quite long span. It makes a quite strong load for over bridge structure. Depends on this case, this thesis will held about re-planning Mahakam IV Twin Bridge in Samarinda City with different system, which is over bridge structure will able to pass just using pylon and cable, that is Cable Stayed Bridge with Two Vertical Planes System Type Fan.From the planning result, the result of the top structure planning for girder using the Girder Prestress Box, Cable using VSL SSI 2000 Stayed cable System, Pylon Structure 5 mx 5 m with 100 D-32 and lower structure for pylon foundation using 36 steel piles 100 cm with a depth of 60 m.